Optimization of Ammonia Removal from Landfill Leachate by Aeration Using Response Surface Methodology (RSM) - Husin, Haslina; Ishak, Norfatiha; Jamian, Nor Ruwaida; Naidu, Dewika; Mohd Rashid, Ammar; Yusuf, Sara Yasina; Abdul Manaf, Norhuda (International Journal of Integrated Engineering, 2024)
Landfill leachate has a high concentration of ammonia, making it a harmful pollutant for both surface and groundwater. One of the most favoured methods for removing ammonia from leachate is aeration, as it has been proven to remove a significant amount of ammonia in the most efficient and economical way. The effect of operational variables on ammonia removal efficiency by aeration was investigated in the current study by applying Response Surface Methodology (RSM) approach. Three operating parameters such as airflow rate, aeration time and lime dosage were investigated to achieve the optimization of ammonia removal. The optimal parameters for a favourable reaction of ammonia-nitrogen (NH3N) removal were found to be 6 L/min airflow, 90 minutes aeration time, and a lime dosage of 6 g/L. At these ideal conditions, Quadratic RSM predicted a maximum NH3N removal of 98.0%, which has been validated by the experiment and successfully removed 97.6%. The finding also showed that airflow rate and aeration time were more significant than lime dosage for NH3N removal. Due to increased contact time between air and liquid, regardless of the amount of lime used, increasing the aeration period ammonia removal efficiency. Considering the influential factors, determining the optimum condition for ammonia removal by aeration will explain the potential interferences that may inhibit the efficient recovery of NH3N. Hence, aeration is a promising approach for ammonia removal from landfill leachate.